Demolition, rehabilitation, and conservation: heritage in Shanghai’s urban regeneration, 1990–2015 - Zhong, Xiaohua; Chen, Xiangming (Journal of Architecture and Urbanism, 2017)
Urban heritage sites in central cities are most difficult to protect during rapid and large scale urban (re)development. Rising land values from property development conflict with and constrain heritage preservation. Compared with many cities in developed and developing countries, large Chinese cities have experienced a stronger redevelopment imperative, faster population growth, and a weaker concern for urban heritages over the last three decades. We use Shanghai to examine the contested evolution of heritage preservation against massive urban redevelopment through three stages from 1990 to the present. Using three heritage projects (Xintiandi, Tianzifang, Bugaoli), we focus on: 1) how each project was implemented and the economic and spatial outcomes each has produced; 2) how the mode of each project’s development interacted with the shifting official policies for heritage preservation; and 3) the implications of the findings, theoretical and practical, for more effective urban preservation.